Investigation of ionospheric response to a moderate geomagnetic storm over the mid-latitude of Saudi Arabia - Alenazi Moqbil Salem; Nooreldeen Hassan Mahdy; Ahmed Ayman Mahmoud; Yossuf Mohamed; Lomotey Solomon Otoo; Yassen Ahmed; Mahrous Ayman (Open Astronomy)
This study investigated the ionospheric response to a moderate geomagnetic storm recorded on May 14, 2019, with a minimum disturbance storm time (Dst) index of −70-70 nT. Observations from three Global Positioning System (GPS) stations (RFHA, 29.6∘{\text{29.6}}^{° }N; ARAR, 30.9∘{\text{30.9}}^{° }N; TRIF, 31.6∘{\text{31.6}}^{° }N) in Saudi Arabia’s Northern Borders Province were used to derive the vertical total electron content (VTEC), revealing a significant increase during the storm’s main phase. A comparative analysis of GPS-derived VTEC with the International Reference Ionosphere 2016 (IRI-2016) model showed that IRI-2016 tends to overestimate VTEC during quiet and disturbed geomagnetic conditions. Additionally, GPS-VTEC data were utilized to detect traveling ionospheric disturbances within 30 min, moving poleward across the Northern Arabian Peninsula throughout the storm. These findings highlight the impact of the geomagnetic activity on ionospheric dynamics and the effectiveness of the new GPS stations in monitoring ionospheric behavior over the Arabian Peninsula.